Synthesis, Antitumor Activity and Preliminary Structure-activity Relationship of 2-Aminothiazole Derivatives - Li, Hongshuang; Wang, Xinran; Duan, Guiyun; Xia, Chengcai; Xiao, Yuliang; Li, Furong; Ge, Yanqing; You, Guirong; Han, Junfen; Fu, Xiaopan; Tan, Shanhui; Wang, Rongwei (Chemical research in Chinese universities, 2016)
In this paper, we described the synthesis of 2-aminoflfiazole sublibrary containing methyl, bromo, phenylor butylidene at 4- or/and 5-position of its core. All target compounds were evaluated tbr their antitumor activitiesagainst human lung cancer cell line H1299 and human glioma cell line SHG-44. Among the compotmds screened,4,5,6,7-tetrahydrobenzo[d]thiazole（26b） exhibited the most potent antittunor activities with IC50 values of 4.89 and4.03 μmol/L against the two tested cell lines, respectively. Preliminary structure-activity relationship（SAR） studies ofthese compound were subsequently investigated.